President's Message - Dale, Ernest (Academy of Management Journal, 1968)
The article presents a letter from the president of the Academy of Management on the topic of the financial support of management research. The author notes that much of the money given to support research is concentrated in the areas of behavioral and quantitative research rather than operational objectives and much is directed towards individuals rather than organizations. The author proposes an audit of the quality of research and the teaching of management and asks members to share their thoughts on the most significant writings since 1900 in the field of management.